2014
DOI: 10.4236/ojim.2014.41004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cardiac Rehabilitation Program in Patients with Congenital Heart Disease

Abstract: The beneficial effects of the programs of cardiac rehabilitation in adults are widely known. Nevertheless, the accomplishment of these programs in patients with congenital heart is scarcely developed. In this study, we want to evaluate the preliminary results of a program of cardiac rehabilitation. Patients and methods: Thirty-three patients aged 8 to 40 completed the rehabilitation program. Thirty-one of them had an operated congenital heart disease, one had an implantable cardioverter defibrillator, and anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(16 reference statements)
0
3
0
3
Order By: Relevance
“…Advances in prenatal diagnosis, that have enabled earlier detection of foetal anomalies [23, 28–31], specifically in Spain [32–34], plus advances in surgical intervention techniques [13, 14, 20, 35], also in Spain [36], are the main factors identified as being responsible for the decrease in mortality. In addition, this downturn has also been influenced by the implementation of and improvement in cardiac rehabilitation programmes [3739] coupled with ambulatory management and follow-up [40].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in prenatal diagnosis, that have enabled earlier detection of foetal anomalies [23, 28–31], specifically in Spain [32–34], plus advances in surgical intervention techniques [13, 14, 20, 35], also in Spain [36], are the main factors identified as being responsible for the decrease in mortality. In addition, this downturn has also been influenced by the implementation of and improvement in cardiac rehabilitation programmes [3739] coupled with ambulatory management and follow-up [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our data add to the findings of other small studies that have demonstrated some degree of benefit of CR programs in ACHD patients. In a study of 57 ACHD patients ≥12 mo after having surgery to close a ventricular septal defect or atrial septal defect, 1 mo of a comprehensive CR program resulted in an improvement in PA and reducing fears concerning various forms of PA. 5 Another study by Dedieu et al 6 to great complexity congenital heart disease and found that completing a full CR program was associated with a higher exercise capacity. Most recently, Opotowsky et al 8 evaluated 28 ACHD patients who were randomized to a 12-wk clinical CR program versus standard of care and demonstrated improved aerobic capacity and self-reported health status in those who completed CR.…”
Section: Discussionmentioning
confidence: 99%
“…Estos estudios demuestran evidencia en favor de la prescripción de la rehabilitación cardiaca sea indicada en pacientes con cardiopatía congénita corregida. (López-Jiménez, y otros, 2013) (Dedieu, Fernández, Garrido-Lestache, Sánchez, & Lamas, 2014) (Gierat-Haponiuk, y otros, 2015.El principio básico de la cánula de alto flujo consiste en ofrecer un gas fresco, caliente y húmedo, el cual se administra en un caudal de flujo alto a través de un diseño especial similar a la cánula nasal convencional. El gas se humidifica (humedad relativa 95-100%) y se calienta hasta un valor cercano a la temperatura corporal (34-40°C).…”
Section: Introductionunclassified